Evaluation of injectable platelet-rich fibrin produced by a simple twice-centrifugation method combined with vacuum sealing drainage technology in the treatment of chronic refractory wounds - Xue, Xin; Bian, Yuling; Yang, Meng; Wei, Wei; Meng, Lingmin; Zhang, Qingfu; Tao, Jianguang (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: To evaluate the effects of injectable platelet-rich fibrin (i-PRF) produced by a simple twice-centrifugation method combined with vacuum sealing drainage on wound inflammation and scar formation in chronic refractory wounds (CRW). Methods: A total of sixty-eight patients with CRW who were admitted to our hospital were enrolled in this study. They were then randomly divided into the study group (n=34) with being treated using negative pressure sealing and drainage technology, and the control group (n=34) with being treated using injectable platelet-rich fibrin in conjunction with negative pressure sealing and drainage technology. The following were the primary outcomes: scar conditions at 1 and 3 months after the wound was fully healed, wound healing time, hospitalization time, wound healing rate, incidence of adverse reactions, serum inflammatory indices, and pain levels were assessed 1 day before treatment and 14 days after treatment. The secondary outcomes were determined by comparing the proportion of positive bacterial cultures in the two groups on the day before therapy, as well as on the seventh and fourteenth days after treatment. Results: The wound healing time and hospital stay in the study group were significantly lower than that in the control group (all P<0.001). The wound healing rate of the study group was significantly higher than that of the control group on the 14th day and 28th day after treatment (all P<0.001). On the 14th day after treatment, the levels of WBC, CRP, and IL-6 in the study group were lower than those in the control group (all P<0.001). The positive rate of bacterial culture in the study group was significantly lower than that in the control group on the 7th and 14th day after treatment (all P<0.05). At 1 month and 3 months after treatment, the VSS score in the study group was lower than that in the control group (all P<0.001). The total defect rate of the study group was also significantly lower than that of the control group (5.88% vs 29.41%, P=0.011). Conclusion: The i-PRF produced by simple twice-centrifugation method combined with VSD could reduce wound inflammation and improve scar formation in patients with CRW.